Can categorised values of maximal oxygen uptake discriminate patterns of exercise dysfunction in pectus excavatum: a prospective cohort study?. Issue 1 (6th August 2021) - Satur, Christopher M R; Cliff, Ian; Watson, Nicholas
Abstract : Cohort studies of patients with pectus excavatum have inadequately characterised exercise dysfunction experienced. Cardiopulmonary exercise test data were delineated by maximal oxygen uptake values >80%, which was tested to examine whether patterns of exercise physiology were distinguished. Methods: Seventy-two patients considered for surgical treatment underwent assessment of pulmonary function and exercise physiology with pulmonary function tests and cardiopulmonary exercise test between 2006 and 2019. Seventy who achieved a threshold respiratory gas exchange ratio of >1.1 were delineated by maximal oxygen uptake > 80%, (group A, n=33) and <80% (group B, n=37) and comparison of constituent physiological parameters performed. Results: The cohort was 20.8 (±SD 6.6) years of age, 60 men, with a Haller's Index of 4.1 (±SD 1.4). Groups A and B exhibited similar demography, pulmonary function test results and Haller's index values. Exercise test parameters of group B were lower than group A; work 79.2% (±SD 11.3) versus 97.7 (±SD 10.1), anaerobic threshold 38.1% (±SD 7.8) versus 49.7% (±SD 9.1) and O2 pulse 77.4% (±SD 9.8) versus 101.8% (±SD 11.7), but breathing reserve was higher, 54.9% (±SD 13.1) versus 44.2% (±SD 10.8), p<0.001 for each. Both groups exhibited similar incidences of carbon dioxide retention at peak exercise. A total of 65 (93%) exhibited abnormal values of at least one of four exercise test measures. Conclusion: This study showed that patients with pectus excavatum exhibited multiple physiological characteristics of compromised exercise function. It is the first study that defines differing patterns of exercise dysfunction and provides evidence that patients with symptomatic pectus excavatum should be considered for surgical treatment.